2008 IEEE International Conference on Robotics and Biomimetics 2009
DOI: 10.1109/robio.2009.4912981
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical biomechanical model of the shoulder: Null space based optimization of the overactuated system.

Abstract: A new dynamical model of the shoulder has been developed. It consisted of eleven muscles. The glenohumeral joint is modeled as a spherical joint, allowing for three rotations. Muscle wrapping around a spherical humeral head is calculated analytically. The problem of indeterminated muscle forces is solved in two steps. First, an intermediate solution is calculated using the pseudo-inverse of the moment arms matrix providing the mapping between the muscle forces (actuators) and the generalized forces (system). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The null-space method was used both because it has shown promising results (Aeberhard et al 2009;Terrier et al 2010) and because it helped to pinpoint the nature of the unfeasibility observed in Ingram et al (2012) due to its direct use of the map (13) to construct the solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The null-space method was used both because it has shown promising results (Aeberhard et al 2009;Terrier et al 2010) and because it helped to pinpoint the nature of the unfeasibility observed in Ingram et al (2012) due to its direct use of the map (13) to construct the solution.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed presentation of this re-parameterisation is given in Aeberhard et al (2009) andTerrier et al (2010).…”
Section: Null-space Optimisationmentioning
confidence: 99%
“…The vectort a is the torques around the inertial frame axes centred at each of the three joints. The matrix W 0 ðkÞ is the generalised moment-arm matrix resulting from the projection of the moment-arms WðkÞ into the generalised coordinate space (Aeberhard et al 2009;Ingram et al 2013aIngram et al , 2013b. The projection matrix P 0 ðkÞ is defined as the partial derivative of the rotational velocity vectors with respect to the coordinate velocities (Aeberhard et al 2009).…”
Section: A Musculoskeletal Model Of the Human Shouldermentioning
confidence: 99%
“…This approach has been applied in a variety of application fields, ranging from the analysis of gait [2] and running [3], to the study of upper limb movements [4]. For instance, different studies in the literature proposed a biomechanical model of the human shoulder complex, for quasi-static and dynamic estimation of the muscle forces and joint reaction forces in the gleno-humeral joint, combining inverse dynamics and static optimization to estimate the associated muscle forces [5][6][7]. Other studies present a conceptual 3D bipedal nonlinear model for Sit-To-Stand task with optimal controller design for exoskeleton torques [8] or a coupled optimization problem for a 2D model to solve for controller, which shows that central nervous system is able to solve the limb coordination problem when recovering from balance perturbations [9].…”
Section: Introductionmentioning
confidence: 99%